Exploring the Relevance of Pandit Deen Dayal Ji's Educational Thoughts in the Contemporary Educational Landscape - Dwivedi, Rajni; Singh, Vipin Kumar (CV. Rayyan Dwi Bharata, 2026)
This study explores the relevance of Pandit Deen Dayal Ji's educational thoughts in the contemporary educational landscape, focusing on his key principles of integral humanism and value-based education. The objectives are to analyse the historical context of his ideas, examine their application in modern educational settings, and identify challenges and opportunities in implementing these principles today. A comprehensive review method was employed, analysing literature from educational texts, scholarly articles, and case studies of institutions applying these principles. The findings reveal that while his thoughts are highly relevant, their application faces challenges due to changing societal values and educational priorities. However, opportunities exist to enhance the current educational system by incorporating his emphasis on holistic development and ethical education. The study suggests integrating these principles into curricula to foster a more inclusive and value-driven educational environment. This research contributes to understanding how traditional educational philosophies can be adapted to meet modern needs.